Quasi-stationary mode of the beam-plasma discharge - Dadyka, D.I.; Anisimov, I.O. (Вопросы атомной науки и техники, 2018)
Results of the beam-plasma discharge simulation are presented for the plane 2D model. Simulation was carried out using non-relativistic electrostatic package. Elastic collisions between electrons and neutral molecules, excitation and ionization of neutral molecules and radiative recombination were taken into account. Quasi-stationary stage of the discharge was achieved.